2021
DOI: 10.1177/11786302211043660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Level of Pesticides in the Blood of Small-Scale Farmers and Its Associated Risk Factors in Western Ethiopia

Abstract: Background: The presence of agricultural pesticide residue can cause adverse health effects.The main objective of this study was to evaluate the level of pesticides in the blood of small-scale farmers (SSFs) and associated risk factors in western Ethiopia. Methods: Across sectional study was conducted in June 2020 using 240 blood samples, 140 from the exposed small-scale farmers (ESSFs) and 100 from non-exposed small-scale farmers (NESSFs). The blood sample analysis was mad for 5 organochlorines (OCs) and 3 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…This reveals that younger groups would be convenient for the recommended PPE on pesticides use as compared to older SSFs who could use more pesticides to maximize their products 18 and due to bioaccumulation of pesticides from past exposure and decreasing rates of excretion with increasing age for small-scale farmers. 21,32…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This reveals that younger groups would be convenient for the recommended PPE on pesticides use as compared to older SSFs who could use more pesticides to maximize their products 18 and due to bioaccumulation of pesticides from past exposure and decreasing rates of excretion with increasing age for small-scale farmers. 21,32…”
Section: Discussionmentioning
confidence: 99%
“…40 Moreover, mixing the pesticides with bare hands, not wearing PPE, and carelessly disposing of leftover pesticides 42 causes high exposure of SSFs to pesticide chemicals. 21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, many concerns have arisen worldwide about the negative impacts of pesticides on the environment and human health. In particular, agricultural region residents are a highly exposed population, with higher quantification frequencies and levels of pesticides found in various environmental media from rural areas, such as air [ 15 , 16 ], dust [ 17 , 18 , 19 ], silicone wristbands [ 20 , 21 ], and human samples such as urine [ 22 , 23 , 24 ] and blood [ 25 , 26 ]. In addition, several epidemiological studies have found an association between residential proximity to agricultural fields and diseases such as autism [ 27 , 28 ], Parkinson’s disease [ 29 ], childhood cancer [ 30 , 31 ], and also with neurobehavioral effects [ 32 ].…”
Section: Introductionmentioning
confidence: 99%